Analysis of role institutional Hambalang Village in tourism development through community empowerment - Yustisia Pasfatima Mbulu; Fetty Nurmala Rossi; Yosi Erfinda; Aqilla Devia Salsabila (Universitas Merdeka Malang, 2023)
The development of a tourist village is influenced by institutional aspects, tourist attractions and infrastructure. One important component in the success of tourism is an institution. The purpose of this study is to analyze the institutional role of Hambalang Village to empower the community in providing homestays, developing UMKM, culinary tourism, religious tourism, and sports tourism. This research method using qualitative methods with a descriptive approach. This research data collection method through observation, interviews, and literature study. The data sources in this study were obtained from Focus Group Discussion (FGD) activities obtained from Hambalang Village institutions which included the Village Government, BUMDes, LPM, and BPD. The results of the analysis show that there is an institutional role in Hambalang Village in the development of UMKM, culinary tourism, religious tourism, and sport tourism. However, it cannot be ruled out that there is no institutional role for Hambalang Village in providing homestays. Efforts to develop tourism through community empowerment in Hambalang Village in the development of UMKM and religious tourism that play a major role are the Village Government and BPD. Meanwhile BUMDes and LPM focus on culinary tourism. While community empowerment for sport tourism is mostly carried out by the Village Government.